Synthesis and characterization of Cu(II) complexes of pyrazine-2,3-dicarboxylicacid - YALÇIN, BAHATTİN; KAKI, ESRA HACER (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Four copper(II) coordination polymers, {[Cu(pz(COO)(2))(H2O)](4)center dot HBr}(n) (1). {[Cu(pz(COO)(2))(NH3)(2)]center dot H2O}(n) (2), {[Cu3H2(pz(COO)(2))(4)(H2O)(3)]center dot 2H(2)O}(n) (3) and {[Cu-2(pz(COO)(2))(2)(NH3)(2)(H2O)(3)][Cu(pz(COO)(2))(NH3) (H2O)(2)][Cu(pz(COO)(2))(NH3)(H2O)]center dot 2H(2)O}(n) (4) were synthesized using pyrazine-2,3-dicarboxylic acid, CuBr2, 2-(2-aminoethylamino)ethanol/triethanol amine/ammonia in a methanol:water (1:1) solution, and the mixed ligand complexes were characterized by spectroscopic methods, thermal and elemental analysis, and magnetic susceptibility. Complexes 2 and 4 were also characterized by means of single crystal X-ray crystallography. The characterizations show that the complexes have polynuclear molecular structures, except for complex 2, and all of the complex structures form polymeric chains. Complex 4 has a pseudo-merohedral twin structure. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Pyrazine-2,3-dicarboxylic acid; Copper(II) bromide complexes; Copper(II) mixed ligand complexes; Twin structure; COPPER(II) COORDINATION POLYMER; RAY CRYSTAL-STRUCTURE; MAGNETIC-PROPERTIES; 2,3-PYRAZINEDICARBOXYLIC ACID; STRUCTURAL-CHARACTERIZATION; MOLECULAR-STRUCTURE; LIGANDS; DINUCLEAR; ADDUCTS